1990
DOI: 10.1080/00914039008041068
|View full text |Cite
|
Sign up to set email alerts
|

Structural-Chemical Conception of Stabilization of Aromatic Polymers as Exemplified by Arylene Carboranes

Abstract: The paper discusses the specific features of thermal behaviour of carborane-containing polymers and the stabilizing effect of the carborane groups as exemplified by arylene carboranes. The results obtained explain as a whole the stabilizing effect of aromatic polymers by carborane-containing additives.At the present time the requirements for a prolonged thermal stability of polymers, the working temperatures of the corresponding composites, considerably exceed those of the stability of chemical groups and chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The inductively electronwithdrawing carboranes typically increase the stability of pyrrole and polypyrroles by decreasing their reactivity towards electrophiles and oxidizing agents. To date, several carborane-containing polymers have been synthesized and characterized [11][12][13]. These macromolecular systems show high resistance to combustion and unique two-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…The inductively electronwithdrawing carboranes typically increase the stability of pyrrole and polypyrroles by decreasing their reactivity towards electrophiles and oxidizing agents. To date, several carborane-containing polymers have been synthesized and characterized [11][12][13]. These macromolecular systems show high resistance to combustion and unique two-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such functional groups could confer on the host matrix novel properties, such as a thermal and/or chemical stability, optoelectronic characteristics, and an ordered structure. For instance, numerous polymers in which the icosahedral carboranes were linked by aromatic units (generally benzene) have been synthesized and characterized. These macromolecular systems showed either an extreme resistance to combustion 3,6 or a two-dimensional grid-shaped structure using the boron cage as a molecular connector . Other poly(carborane−siloxane) elastomers incorporating acetylenic units showed also remarkable thermal and oxidative stabilities …”
Section: Introductionmentioning
confidence: 99%
“…The icosahedral boron cluster, o -carborane (C 2 B 10 H 12 ), displays unique electronic, steric, and chemical properties, including high hydrophobicity, high thermal and chemical stabilities, and three-dimensionally delocalized electrons. Carboranes have been combined with conjugated systems in an attempt to provide thermal stability to semiconducting polymers. Incorporating carborane into conjugated backbones also drastically influences the emission properties of these systems, which are influenced by the dihedral angle between the carbon–carbon bond in carborane and the π-conjugated unit . For this reason, carborane has been widely studied in many conjugated monomer and polymer systems with aromatic building blocks including p -phenyleneethynylene, ,, naphthalene, carbazole, , and triphenylamine, to name a few. ,,,, These studies have shown that introducing carborane into a conjugated system can cause the system to experience excimer emissions, AIE, crystallization-induced emission, ICT, and twisted ICT, in addition to the local emission of the conjugated building block.…”
Section: Introductionmentioning
confidence: 99%